The Role of Agribusiness Support Institutions in Increasing Hybrid Maize Farming Production in Marobea Village Sawerigadi Sub-district, West Muna District - Risma Lawanti; Azhar Bafadal; La Ode Alwi (International journal of technology and education research, 2024)
This study is motivated by the increasing production of hybrid corn crops in the West Muna region, which has been on the rise. In 2017, the Central Bureau of Statistics (BPS) recorded corn productivity in West Muna reaching 11,378.84 tons/ha, and it increased to 20,221.17 tons/ha in 2018 but declined in 2019 and 2020 to 11,975.63 tons/ha. Due to the decline in corn farming production, farmers' welfare also decreased. Therefore, the role of institutions in supporting the agribusiness system is crucial to significantly improving the welfare of farming communities. This research aims to determine: (1) The role of institutions in increasing production outcomes among corn farmers in Marobea Village, Sawerigadi District, West Muna Regency. (2) The relationship between the role of farmer groups and the increase in corn farming productivity in Marobea Village, Sawerigadi District, West Muna Regency. This research was conducted from January to July 2024. The population in this study consists of hybrid corn farmers who are members of farmer groups, agricultural extension officers, farmers' association groups (Gapoktan), financial institutions, and middlemen. This study employs descriptive analysis and Spearman rank correlation techniques. The results of the study show that (1) The role of agribusiness support institutions in hybrid corn farming in Marobea Village, Sawerigadi District, West Muna Regency: farmer groups are categorized as having a fairly significant role, Gapoktan is categorized as not having a role, agricultural extension officers are categorized as having a fairly significant role, middlemen are categorized as having a fairly significant role, and financial institutions are categorized as having no role. (2) Based on the Spearman rank correlation test, the relationship between learning classes and productivity scored 0.668, the relationship between farming production units and productivity scored 0.471, and the relationship between cooperation platforms and productivity scored 0.645, with each showing a positive and significant relationship